2013
DOI: 10.4161/derm.24807
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status among healthy postmenopausal women in South America

Abstract: Vitamin D status has been extensively studied throughout the world. However, most of the studies are from North America, Europe and Oceania. This review describes published evidence on vitamin D status among healthy postmenopausal women in South America, where food is not fortified with vitamin D. A literature search identified ten studies from only three countries in the region: Argentina, Brazil and Chile. These studies reported a high prevalence of vitamin D deficiency, in spite of their location at latitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
0
5
0
2
Order By: Relevance
“…The prevalence was found to be 22.7% in South Australia ( 15 ), 24% in Brazil ( 16 ), while the prevalence of vitamin D deficiency in adolescents was found to be 45.4 % in the United Arab Emirates ( 17 ). Nevertheless, the prevalence of vitamin D deficiency was 78.1% in females and 72.4% in males in Saudi Arabia, located in the Middle East as is the United Arab Emirates ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence was found to be 22.7% in South Australia ( 15 ), 24% in Brazil ( 16 ), while the prevalence of vitamin D deficiency in adolescents was found to be 45.4 % in the United Arab Emirates ( 17 ). Nevertheless, the prevalence of vitamin D deficiency was 78.1% in females and 72.4% in males in Saudi Arabia, located in the Middle East as is the United Arab Emirates ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D 3 , whose active form 1,25(OH) 2 D 3 is a cofactor required for calcium absorption in the gastrointestinal tract, is also strongly correlated with bone density [ 59 ]. Vitamin D insufficiency (25(OH)D 3 serum levels <50 nmol/L) is also not uncommon due to diet, lack of sun exposure, or genetic mutations [ 60 ], and many studies have shown that the majority of postmenopausal women in areas around the world have insufficient vitamin D levels [ 61 , 62 , 63 ].…”
Section: Reviewmentioning
confidence: 99%
“…However, data obtained from various populations of community-living postmenopausal women with or without osteoporosis highlight a wide disparity of prevalence rates of 25(OH)D concentration ≤ 20 ng/mL depending on the considered geographical areas [ 7 , 8 ]. For instance, in a European study involving more than 8500 postmenopausal women, the prevalence of 25(OH)D deficiency reached 32.1% when considering the cutoff value of 20 ng/mL [ 9 ], while in Indian, Chinese, and US populations of postmenopausal women, the estimated prevalence rates were 53.3%, 72.1%, and 53%, respectively [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%